Factors Influencing the sales performance of Honda Malaysia Sdn. Bhd. / Nurshamimah Samsuddin (Faculty of Business and Management, 2008)
The focus of this study is on the factors that influence sales performance of Honda Malaysia Sdn. Bhd. This is because since began their operation in Malaysia, there are increasing number of road users that using Honda Cars Brand. Therefore, this research is conduct to find out what are the factors of this scenario. The research objectives are to determine whether the sales performance of Honda Malaysia Sdn. Bhd. Can be influence by the availability of product, to identify whether the positive word of mouth that can affect to increase the sales performance and also to examine whether the disposable income that can influence sales performance. This research use exploratory because an exploratory study is conducted to define and identify on certain object. As in this research, it uses to identify the factors that influence the sales performance of Honda Malaysia Sdn. Bhd.. This type of research is different from conclusive research that used to find decision; it is focus more to identify the information needed for subsequent research. The secondary data that gathered in this research is collected from various sources such as journals, articles, newspaper cutting, Malaysia Automotive Association and Production Control Department.